2020
DOI: 10.1016/j.brainres.2018.07.026
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of orexins to sex differences in the stress response

Abstract: Women are twice as likely as men to suffer from stress-related psychiatric disorders, such as post-traumatic stress disorder (PTSD) and Major Depressive Disorder (MDD), however, the biological basis of these sex differences is not fully understood. Interestingly, orexins are known to be dysregulated in these disorders. This review first discusses the important role of orexins regulating the response to stress. Next, we review the evidence for sex differences in the orexin system, in which the majority of both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 97 publications
2
23
0
Order By: Relevance
“…The clinical evidence implicating ORX in PD is important 11,51 and our results showing that NMS augments ORX A levels in the hypothalamus are consistent with clinical and preclinical data. A similar increase has been reported in males 18 but since regulation of ORX neurons likely differs between sexes 19,22 , testing this effect in females was necessary. ORX synthesis is activity-dependent and highly plastic 52 .…”
Section: Neonatal Maternal Separation Augments Orx Activation Under Bsupporting
confidence: 62%
See 1 more Smart Citation
“…The clinical evidence implicating ORX in PD is important 11,51 and our results showing that NMS augments ORX A levels in the hypothalamus are consistent with clinical and preclinical data. A similar increase has been reported in males 18 but since regulation of ORX neurons likely differs between sexes 19,22 , testing this effect in females was necessary. ORX synthesis is activity-dependent and highly plastic 52 .…”
Section: Neonatal Maternal Separation Augments Orx Activation Under Bsupporting
confidence: 62%
“…The prevalence of PD is 2-3 fold greater in women than in men, yet most of our basic knowledge arises from experiments performed on males despite strong evidence indicating that endocrine regulation of ORX neurons is sex-specific 22,23 . This is an important issue because clinical observations point to an important role of ovarian hormones in the pathophysiology of PD.…”
Section: Introductionmentioning
confidence: 99%
“…Another group has shown that administration of the OXA peptide in the cerebral ventricles elicits anxiety-like behaviors in both mice and rats ( Suzuki et al, 2005 ). There is also preclinical and clinical evidence that an enhanced level of orexin activity may contribute to the higher incidence of anxiety in females ( Grafe and Bhatnagar, 2020 ).…”
Section: Orexin Neurotransmission To the Pvt And Stress-induced Anxiementioning
confidence: 99%
“…Finally, the results’ generalizability to females should also be assessed in the light of preclinical and clinical evidence for higher orexin system expression in females. 56 …”
Section: Discussionmentioning
confidence: 99%